Thermal and Heavy Metal Ions Pollution Assessment in Near By Water Bodies of Vijayawada Thermal Power Station - Hanumantha Rao, Y.; Ravindhranath, K. (Asian Journal of Chemistry, 2012)
A thorough study is made to assess the thermal and metallic ion pollution caused by Vijayawada thermal power station in the surrounding water bodies. Surface and ground water samples at judicially chosen sample stations have been analyzed at specific intervals of time for a period of nine months. It is found that the surface and ground waters are being contaminated with respect to heavy metal ions. Stratification of impounded waters of Krishna river at the point of discharge of effluents, is observed due to elevated temperatures and it is resulting in the depletion of dissolved oxygen content and thereby causing stress on biota of the lake; valuable fish species are being disappeared from placid waters of Krishna river and causing the migration of fisher man for their lively hood. Further, it is observed that heavy metal ions like Cr, Mn, Fe, Ni, Cu and Zn are being leached from fly ash due to the anaerobic conditions prevailing in the bottom of stratified pond waters. The accumulation of these ions due to bio-amplifications signals the alarming situation ahead for the people in five costal districts in Andhra Pradesh as the same impounding waters are being supplied for their drinking and agricultural purposes.